Pertemuan Ilmiah PERDAMI Cabang DIY : Penyakit alergi dan inflamasi pada mata - [Tidak Terdaftar] ([Tidak Terdaftar], 2001)
Pertemuan Ilmiah PERDAMI Cabang DIY : Penyakit alergi dan inflamasi pada mata